Extended Kalman Filter (EKF)-based modular-stack Vanadium Redox Flow Battery (V-RFB) prediction model development for reducing electrode contact resistance and parallelization current - Mohamed, Mohd Rusllim; Ramli, Noor Lina; Razali, Saifudin; Sulaiman, Mohd Herwan; Abu Seman, M. N.; Azizan, Ahmad (2013)
Vanadium Redox Flow Battery (V-RFB) is a type of rechargeable flow battery that employs vanadium ions in different oxidation states. It undergoes oxidation and reduction reaction during discharge and charge process at anode and cathode. Presently, there are lack of publication studies on electrical circuit model for V-RFB. Electrochemical model is commonly use to represent battery due to its detailing in electrochemical process, however, the model is not suitable to identify electrical behavior of V-RFB. Parameter estimation on battery model is a process to fit an equivalent circuit into the battery. This thesis presents equivalent electrical circuit consists of actual and approximate circuit for V-RFB as well as hydrodynamics behavior of the Vanadium redox flow battery (V-RFB) by using 3D computational fluid dynamics (CFD) models. The aim of this project is to propose equivalent electrical circuit for V-RFB that represents excellent adaptableness to any circuitry analysis and design and to study the pump power (pump energy consumption) and electrolyte flow distribution required within the cell.